DEVELOPMENT OF SCIENCE PROCESS SKILLS AND LEARNING ACHIEVEMENT OF MATHAYOMSUKSA 4 STUDENTS ON THE UNIT OF ATOMS AND ELEMENT PROPERTIES BY USING STEM EDUCATION LEARNING MANAGEMENT - Nantabhut, Jintana; Suwannatrai, Kulwadee; Wattanasarn, Hassakorn (Journal of Graduate School Sakon Nakhon Rajabhat University, 2025)
This research aimed to 1) develop the STEM Education lesson plans on the unit of Atoms and Element Properties to achieve an efficiency rate of 80/80, 2) compare the students’ science process skills before and after the intervention, and 3) explore the student satisfaction level with the STEM Education learning management. The sample consisted of 17 Mathayomsuksa 4 students from Laopacha–utid School under the Secondary Educational Service Area Office, Mukdahan, during the second semester of the 2023 academic year. The instruments used for data collection included lesson plans based on STEM education learning management, a science process skills test, a learning achievement test, and a satisfaction questionnaire. The statistics included percentages, means, standard deviations, and t–test for Dependent Samples. The research results revealed that the developed STEM education lesson plans on the unit of Atoms and Element Properties achieved an efficiency rate of 83.87/82.45, surpassing the established criteria of 80/80. Post-intervention assessments revealed statistically significant improvement at the .01 level of significance in both students’ science process skills and learning achievement compared to pre–pre-intervention levels. Furthermore, students expressed the highest level of satisfaction with the STEM education learning management ( = 4.85, S.D. = 0.38).